ANALISIS KEPUTUSAN INVESTASI PROPERTI SYARIAH - Jauhari, Yustika; Khaeruddin, Faizah (ISAFIR: Islamic Accounting and Finance Review, 2026)
This study aims to examine Islamic investment among investors in Islamic property. The population of this study consisted of investors who had invested in Islamic property. Primary data were obtained through questionnaires distributed directly to the respondents. The data were analyzed using descriptive statistical techniques to describe the characteristics of the respondents and the tendencies of their Islamic investment behavior. The results of this study indicate that Islamic investment decisions are based on investors' religious beliefs. Individuals with strong religious convictions tend to align their activities, behaviors, and decision-making processes with the guidelines and principles prescribed by their religion.